Which corporations are likely to engage in LGBTQ+ activism? - Plath, Carolin (2020)
In the past decade corporations have increasingly engaged in social activism, even if it does not relate to their core business. Similarly, CEOs have used their influence to publicly address social issues, such as public policy decisions. Therefore, this paper examines the questions which companies engage in social activism, specifically LGBTQ+ activism. Since CEOs have been more vocal, Upper-Echelon Theory, which states that the values and characteristics of CEOs affect the way an organization behaves, served as the motivation for the research design. The paper looks at LGBTQ+ activism in the form of tweets as the dependent variable, made by the companies in the S&P 500 between 2012 and 2019, in relation to the CEOs leading them. Their age, gender, ethnicity, and political orientation served as the demographic characteristics described in Upper Echelon Theory and as the independent variables tested. The analysis revealed that there is a significant positive relationship between corporate LGBTQ+ activism and liberal CEOs, revealing that the personal politics of the CEOs are an indication for which companies are likely to engage in LGBTQ+ activism. Due to the growing divide between Democrats and Republicans in US politics as well as the partisan approach to social issues this provides insight into where corporate and CEO activism might be headed.